Factors associated with adequate health literacy among type 2 diabetes mellitus patients attending rural government health clinics in Kuala Selangor, Malaysia - Shaharudin, Noor Amanina (2018)
Introduction: Diabetic patients with adequate health literacy are known to have better control of the disease. However, the level of health literacy and the determinants associated with it among rural populations is still questionable in Malaysia. The study aims to determine the level of health literacy with regards to Type 2 Diabetes Mellitus (T2DM) and the factors associated to it among patients attending rural government health clinics in the district of Kuala Selangor. Objectives: To determine the factors associated with the level of health literacy among T2DM patients attending Tanjung Karang and Sungai Tengi Kanan rural government health clinics in the district of Kuala Selangor Methodology: A cross-sectional study using a self-administered questionnaire was conducted with a total of 223 respondents with T2DM. The respondents were selected using systematic random sampling. A validated questionnaire was used and it consisted of socio-demographic, current medical history of T2DM, Michigan Diabetes Knowledge Test (MDKT), MY-TOFHLA, adherence to treatment, Summary of Diabetic Self Care Activity (SDSCA), Diabetic Quality of Life (DQoL), and International Physical Activity Questionnaire (IPAQ). IBM Statistical Package for Social Science (SPSS) Version 23.0 was used to analyse all collected data. The descriptive results were presented as median and interquartile (IQR) and frequency (%). Chi-square test was used to analyse the relationships between dependent and independent variables. For continuous covariates, simple logistic regression was used to determine the relationship with the dependent variable. The predictors were then analysed using multiple logistic regression. Results: The response rate was 86.9%. A total of 85% of the respondents had adequate health literacy. Level Of Education, Household Income, Diabetes Duration, Diabetes Knowledge, SDSCA Exercise, Blood Glucose Testing and Foot Care, and all DQOL domains were significantly associated with the level of health literacy (p <0.05). The odds of having adequate HL is higher among those with Secondary/Tertiary Education [AOR = 5.990, 95% CI (1.301, 22.577), p = 0.022] and household income RM1000 and above [AOR = 4.836, 95% CI (1.152, 20.306), p = 0.031]. The odds of having better exercise score in SDSCA increased by 1.6 times with the increase in 0.5 level of adequate HL [AOR = 1.459, 95% CI (1.101, 2.472), p = 0.015]. Patients are more likely to have increased in score of foot care in SDSCA by 1.4 times with the increase in 0.3 level of adequate HL [AOR = 1.424, 95% CI (1.070, 1.894), p = 0.015]. Conclusion: The prevalence of adequate HL was high among the T2DM patients attending Tanjung Karang and Sungai Tengi Kanan rural government health clinics in the district of Kuala Selangor have adequate HL. The predictors of adequate health literacy are Level Of Education, Household Income and Summary of Diabetic Self Care Activity (SDSCA).